Long-term effects of nurse-led individualized education on middle-aged patients with acute coronary synrome: a quasi-experimental study - Jae Lan Shim; Seon Young Hwang (BMC, 2017)
Abstract Background This study examined the long-term effects of nurse-led, individualized education on self-efficacy, self-care compliance, and health-related quality of life (HRQoL) in middle-aged patients with new-onset acute coronary syndrome. Methods A quasi-experimental pretest-posttest design was used in the study. A cardiovascular nurse provided individualized education to the intervention group (n = 32), and self-efficacy, self-care compliance, and HRQoL at baseline and 3 and 12 months after discharge were compared to those of a control group (n = 30). Patients were recruited from a cardiovascular care unit at a university hospital between 2012 and 2013. Repeated measures analysis of variance was used to compare time-related changes. Results There was no significant difference in self-efficacy between the 2 groups over a fixed period (F = 3.47, p = 0.067) and showed no interaction between the 2 groups (F = 0.45, p = 0.636). However, significant differences were found in the main and interaction effects between the 2 groups and changes in self-care compliance over the follow-up period differed significantly between the 2 groups (F = 28.72, p < 0.001). Changes in mental HRQoL over the follow-up period differed significantly between the 2 groups (F = 33.34, p < 0.001) and significant interaction effect (F = 4.40, p = 0.040). Conclusions Structured nurse-led education should be provided to middle-aged patients with new-onset acute coronary syndrome, as part of routine predischarge education, to increase self-care compliance and mental HRQoL and prevent secondary adverse events. Trial Registration Trial registration number (TRN) is KCT0002454 . The study was registered retrospectively with registration date July 9, 2017.